Outbreak of diarrheal diseases causes mortality in different geographical locations of Bangladesh during the 2021 COVID-19 era - Khan, Ashraful Islam; Islam, Md. Taufiqul; Amin, Mohammad Ashraful; Khan, Zahid Hasan; Qadri, Firdausi (Frontiers in Public Health, 2023)
Objectives: Diarrhoea is a major public health problem in low- and middle-income countries including Bangladesh of the different spectrum of diarrhoeal diseases; cholera occurs every year causing outbreaks and epidemics following a biannual seasonal pattern. Due to the COVID-19 pandemic, hospitalization due to diarrhoeal diseases decreased in 2020 compared to previous years. However, in 2021, massive outbreaks occurred in different geographical locations of the country. We described that an outbreak of diarrhoeal Diseases causes mortality in Different geographical Locations of Bangladesh. Method: Here we present a report of diarrhoea outbreaks that were reported in 2021 in different parts of Bangladesh and data has been captured from different sources like print and electronic media as well as from nationwide surveillance system. Results: Among these locations, districts of Barisal Division, Kishorganj, Noakhali, Gopalganj, Bandarban and Chattogram were the major hotspot of the outbreaks where morbidity due to acute watery diarrhoea and even mortality which is usually low in Bangladesh was recorded. Conclusion: Early detection and prevention and strengthening of the surveillance system is needed to combat the diarrhoeal upsurge for taking immediate control and preventive strategies.